The world crisis and international law : the knowledge economy and the battle for the future / Paul B. Stephan, University of Virginia. - Stephan, Paul B. (Cambridge University Press, 2023)
The knowledge economy, a seeming wonder for the world, has caused unintended harms that threaten peace and prosperity and undo international cooperation and the international rule of law. The world faces threats of war, pandemics, growing domestic political discord, climate change, disruption of international trade and investment, immigration, and the pollution of cyberspace, just as international law increasingly falls short as a tool for managing these challenges. Prosperity dependent on meritocracy, open borders, international economic freedom, and a wide-open Internet has met its limits, with international law one of the first casualties. Any effective response to these threats must reflect the pathway by which these perils arrive. Part of the answer to these challenges, Paul B. Stephan argues, must include a re-conception of international law as arising out of pragmatic and limited experiments by states, rather than as grand projects to remake and redeem the world.